Facile synthesis of Bi2O3/Nylon NCTF and its superior photocatalytic activity against dye degradation. (2020) - Jeyapaul, T.; Latha, P.; Prakash, K.; Selvam, V.
Abstract: In this present work, A novel Bi2 O3 /Nylon NCTF (Nanocomposites Thin Film) has been successfully synthesized via a facile, low cost solution cast method. The as-synthesized Bi2 O3 /Nylon NCTF were characterized by XRD. The morphology was confirmed by scanning electron microscopy. The Bi2 O3 /Nylon NCTF which showed the best photocatalytic activity and superior photocatalytic stability. Synergistic effect of Bi2 O3 /Nylon NCTF played a vital role in photocatalytic degradation Rhodamine Blue (RhB) and Methyl Orange (MO) dyes. This works give a new approach to construct novel photocatalysts and a promising candidate catalyst for removal of hazardous materials from waste water treatment in the near future.